การมีส่วนร่วมทางการเมืองในการปกครองส่วนท้องถิ่นของประชาชนในเขตเทศบาลนครนนทบุรี จังหวัดนนทบุรี - ตุลยสุข สิริชัย (KASEM BUNDIT JOURNAL, 2021)
PURPOSES: To study the level of participation and to compare the political participation in local administration of the people in the Nonthaburi Municipality, Nonthaburi Province. METHODS: Samples consisted of 400 people living in Nonthaburi Municipality. Questionnaire was used for data collection. The data were analyzed by a statistical package of computer programs. Statistical techniques used for data analysis were percentage, mean, standard deviation. The hypotheses were tested by t-test, and F-test (One-Way ANOVA) with statistical significance level at 0.05 level. RESULTS: People had moderate level of political participation in local administration. The results of the hypotheses testing revealed that gender, age, marital status, education level, income, occupation and affiliation were not associated significantly with political participation in the local administration in the Nonthaburi city municipality. CONCLUSIONS: Individual characteristics did not affect political participation in local administration significantly. In order to promote political participation among the people other variables, e.g., political ideology would better be considered.